Ein Bild des Judentums für Nichtjuden von Flavius Josephus : Untersuchungen zu seiner Schrift Contra Apionem - Gerber, Christine. (Arbeiten zur Geschichte des antiken Judentums und des Urchristentums, 1997)
Contra Apionem , the last known work by the Jewish author Flavius Josephus (38 - circa 100 CE), is the only direct Jewish apology, that remains from antiquity. It is of special interest to us, because in its third part Josephus undertakes to explain the main ideas and laws of Judaism and its \'theocratic\' constitution to non-Jewish readers. This volume gives an introduction to Contra Apionem as a whole, a German translation, and a precise analysis and interpretation of the work's third part on Judaism, especially its meaning for non-Jewish readers. This study gives the reader access to an aspect of Josephus and to a part of his important work Contra Apionem , which, to date, have not attracted sufficient scholarly attention.